Stability prediction of five-axis ball-end finishing milling by considering multiple interaction effects between the tool and workpiece. (15th September 2019) - Ji, Yongjian; Wang, Xibin; Liu, Zhibing; Wang, Hongjun; Wang, Kangjia; Wang, Dongqian
Highlights: A new five-axis ball-end milling dynamical model is established. The dynamic characteristics of five-axis milling are investigated. The results show that the model can predict the five-axis milling stability. Abstract: In five-axis ball-end machining, stability of the milling process is not only determined by the combination of depth of cut and the spindle speed, but also determined by the lead and tilt angles of the milling tool (i.e., the tool orientations). As the degree of freedom increases, five-axis machining machines have more complex dynamic characteristics. Therefore, the influence of the tool-workpiece interactions on the machining performance is more obvious. In this paper, a new five-axis ball-end milling dynamical model which considers the multiple interactions between the tool and workpiece is established for the first time. Based on the established dynamical model, the effects of regenerative effect, structural mode coupling and process damping on the dynamic characteristics of five-axis milling are investigated. In addition, the effects of lead angle and tilt angle on the stability prediction of five-axis milling are investigated. The experimental results show that the proposed five-axis milling dynamical model is more reliable than the traditional one in predicting the stability of five-axis milling.